Math Puzzles and Brainteasers : Grades 6-8 : Over 300 Puzzles that Teach Math and Problem-Solving Skills - Stickels, Terry ((Jossey-Bass Teacher. Grades 6-8))
Contenido: 1) Números y operaciones; 2) Geometría y mediciones; 3) Razonamiento matemático; 4) Algebra, estadística y probabilidad. Respuestas.